Long-term ECG monitoring using an implantable loop recorder for the detection of atrial fibrillation after cavotricuspid isthmus ablation in patients with atrial flutter - С. А. Байрамова; А. Б. Романов; С. Миттель; Д. Муссат; Д. Стейнберг; Е. А. Покушалов (Патология кровообращения и кардиохирургия, 2015)
Objective. In patients with atrial flutter who undergo cavotricuspid isthmus ablation, long-term electrocardiographic (ECG) monitoring may identify a new onset of atrial fibrillation (AF). The purpose of our study was to ascertain, through the use of an implantable loop recorder (ILR) with a dedicated AF detection algorithm, the incidence, duration, and burden of new AF in these patients and to develop an optimal post-ablation ECG monitoring strategy. Methods. We enrolled 20 patients with flutter, a CHADS2 score of 2–3, and no prior episode of AF. After cavotricuspid isthmus ablation, we implanted an ILR, which was interrogated routinely in order to evaluate and analyze all stored ECG data. Results. During a mean follow-up of 382±218 days, 3 patterns were observed. First, in 11 (55%) patients stored ECGs confirmed AF at 62±38 days after ablation. Second, in 4 (20%) patients, although the ILR suggested AF, the episodes actually represented sinus rhythm with frequent premature atrial contractions and/or over-sensing. Third, in 5 (25%) patients, no AF was observed. The episodes less than 4 hours were associated with low AF burden (<1%) or false detections. The 1-year freedom from any episode of AF less than 4 and 12 hours was 52% and 83%, respectively. Conclusion. Our data show that many (but not all) patients develop new AF within the first 4 months of flutter ablation. Since external ECG monitoring for this duration is impractical, the ILR has an important role for long-term AF surveillance. Future research should be directed toward identifying the relationship between the duration/burden of AF and stroke and improving the existing ILR technology.